Reimagining Shakespeare's playhouse : early modern staging conventions in the twentieth century - Falocco, Joe (JSTOR EBA., 2010)
Numerous attempts have been made in the modern and postmodern era to recreate the staging conventions of Shakespeare's theatre, from William Poel to the founders of the New Globe. This volume examines the work of these directors, analyzing their practical successes and failures; it also engages with the ideological critiques of early modern staging advanced by scholars such as W.B. Worthen and Ric Knowles. The author argues that rather than indulging in archaism for its own sake, the movement looked backward in a progressive attempt to address the challenges of the twentieth century. The book begins with a re-examination of the conventional view of Poel as an antiquarian crank. Subsequent chapters are devoted to Harley Granville Barker and Nugent Monck; the author argues that while Barker's major contribution was the dubious achievement of establishing the movement's reputation as an essentially literary phenomenon, Monck took the first tentative steps toward an architectural reimagining of modern performance space, an advance which led to later triumphs in early modern staging. The book than traces the sporadic and irregular development of Tyrone Guthrie's commitment to early modern practices. The final chapter looks at how competing historical theories of playhouse design influenced the construction of the Globe, while the conclusion discusses the ongoing potential of early modern staging in the new millennium.